Developing a new performance measure to quantify the difference between actual and predicted on-water rowing performance - Jones, S.; Bailey, C.; Thomas, D.; White, M. G. E.; Rees, P.; Summers, H. D.; Bezodis, N. E. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
This study developed a measure of on-water rowing performance (on-water delta) that quantifies the difference between actual on-water performance and on-water performance as predicted from ergometer performance. Maximal effort 2000 m ergometer and on-water times (n = 340) were collected from 162 athletes over a 16-year period. A linear mixed model was fitted to the dataset to enable predictions of on-water performance from ergometer performance whilst accounting for repeated measures and other factors such as potential environmental effects. On-water delta was defined as a model residual and ranged from -32.8 s (overperformed) to 51.1 s (underperformed). On-water under or overperformance compared to that predicted from ergometer performance could provide valuable context for future biomechanical investigations of on-water rowing technique.